Remoção de nitrogênio de efluente de abate avícola em reator com biofilme em membrana aerada: efeito do tempo de detenção hidráulica e da suplementação de alcalinidade - Rodio, Eliandra (2022)
Wastewater generated in the productive process of poultry slaughtering presents highly polluting potential to hydric bodies for having high concentrations of nutrients as a characteristic, among them, nitrogen. Thus, technologies aimed at the removal of nitrogen are essential for the conservation of water resources and the maintenance of the life of aquatic organisms. Among the technologies for the biological removal of nitrogen, the deammonification process (partial nitritation/ANAMMOX) has been highlighted for promoting the reduction of operating costs in wastewater with a low C/N ratio. Because it is autotrophic, the deammonification process does not require an additional source of carbon, demands low energy costs with aeration, and presents low production of sludge and low emission of greenhouse gases. In this context, this research aimed to evaluate the efficiency of nitrogen removal from poultry wastewater pretreated anaerobically by the deammonification process in a membrane-aerated biofilm reactor (MABR), studying the influence of the hydraulic retention time (HRT) and alkalinity supplementation in the reactor performance, as well as the structure of microbial communities under different operational conditions. The experiment was divided into six phases. The reactor's start-up (phase 1) used synthetic wastewater as feed, with an HRT of 72 hours and later reduced to 24 hours. In phases 2, 3, and 4, wastewater from poultry slaughter began to be used as a substrate, and the HRT adopted was 24, 12, and 36 hours, respectively, with supplemental alkalinity of 1g of NaHCO3 for each liter of wastewater. In phases 5 and 6, the HRT was 24 hours, and the supplemental alkalinity was reduced to 0.65 g.L-1 and 0.30 g.L-1. Among the evaluated phases, phase 5 presented the best nitrogen removal efficiency. In this condition, the average nitrogen removal efficiency was 80.56% and the maximum of 93.18%, corresponding to an average value of nitrogen load removed of 66.93 g N m-3 d-1. Changes in the microbial community were observed with the change of the experimental conditions, for which Candidatus Brocadia was the genus of bacteria with predominant Anammox activity in all the analyzed phases. This study's high performance in biological nitrogen removal demonstrated that the MABR reactor could be a promising alternative for treating poultry slaughterhouse wastewater. Therefore, this research is expected to provide information about the deammonification process and the optimization of operational conditions in future studies aimed at nitrogen removal.